Protestant Theology in Germany During the Past Fifty Years - Obendiek, Harmannus (Scottish journal of theology, 1952)
We may begin our survey of Protestant theology where Karl Barth left it off in Die Protestantische Theologie im Neunzehnten Jahrhundert, which he ended with the observation that for all his popularity and following, Ritschl failed finally to carry the day. Theology moved on beyond his moral evaluation of Christ. Even those under the influence of Ritschl did not simply repeat what he had said—e.g. Wilhelm Herrmann. In May 1900 Adolf Harnack's The Essence of Christianity was published. Harnack's aim was to demonstrate what the various Churches and Christian communities held in common: that God is our Father and the human soul is of infinite value. As to the Gospel of Jesus Christ he declared, ‘Not the Son but the Father alone has a place in the Gospel proclaimed by Jesus’.